2005
DOI: 10.1021/jm050490b
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship Study on a Simple Cationic Peptide Motif for Cellular Delivery of Antisense Peptide Nucleic Acid

Abstract: Improving cellular uptake and biodistribution remains one of the major obstacles for a successful and broad application of peptide nucleic acids (PNAs) as antisense therapeutics. Recently, we reported the identification and functional characterization of an antisense PNA, which redirects splicing of murine CD40 pre-mRNA. In this context, it was discovered that a simple octa(l-lysine) peptide covalently linked to the PNA is capable of promoting free uptake of the conjugate into BCL1 cells as well as primary mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…This behavior is comparable to plain radiolabeled PNAs [23,24]. Conjugation of targeting peptide moieties to PNA significantly increases the kidney accumulation of PNA constructs [14,[17][18][19]29,30,44,87,88]. A preliminary SPECT study in a NMRI, nu/nu mouse was also performed with [ 99m Tc(CO) 3 (Dpa-PNA)].…”
Section: Biodistribution Studies Of [ 99m Tc(co) 3 (Dpa-pna)]mentioning
confidence: 86%
“…This behavior is comparable to plain radiolabeled PNAs [23,24]. Conjugation of targeting peptide moieties to PNA significantly increases the kidney accumulation of PNA constructs [14,[17][18][19]29,30,44,87,88]. A preliminary SPECT study in a NMRI, nu/nu mouse was also performed with [ 99m Tc(CO) 3 (Dpa-PNA)].…”
Section: Biodistribution Studies Of [ 99m Tc(co) 3 (Dpa-pna)]mentioning
confidence: 86%
“…As far as we are aware, LNA/OMe mixmers have not been evaluated in vivo for any application hitherto, but steric block LNA/DNA mixmers containing all phosphorothioate linkages gave efficient splice redirection in mice (Roberts et al 2006). By contrast, PNA and its peptide conjugates have been evaluated in a number of in vivo studies toward splicing redirection (Sazani et al 2002;Albertshofer et al 2005) and cancer (Boffa et al 2005) and have been shown to have wide tissue distribution. Our promising results in cell culture for K-PNA-K3 suggest that relatively simple PNA constructs would be worth evaluating in vivo for microRNA inhibition applications.…”
Section: Discussionmentioning
confidence: 99%
“…85 Albertshofer et al examined stably linked PNA conjugates of variously spaced oligo-Lys peptides by free incubation with cells and showed some small enhancements of splicing redirection in certain cases compared to Lys 8 . 86 Preliminary pharmacokinetic studies of Lys 8 -PNA in mice showed a broad tissue distribution and only modest elimination via excretion within 24 hours. 86 The studies were continued with a series of 28 cationic peptides based on Lys or Arg that had amphipathic character.…”
Section: Steric Block Biological Activities Of Peptide-pna Conjugatesmentioning
confidence: 99%
“…86 Preliminary pharmacokinetic studies of Lys 8 -PNA in mice showed a broad tissue distribution and only modest elimination via excretion within 24 hours. 86 The studies were continued with a series of 28 cationic peptides based on Lys or Arg that had amphipathic character. 87 This work led to improved peptide-PNA conjugates that showed stronger splicing redirection activity at 1-6 mM concentrations without toxicity, but half-lives of the peptide parts of the conjugates in 25% mouse serum were found to be just a few hours or even less.…”
Section: Steric Block Biological Activities Of Peptide-pna Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation